Interaction of VSe2 with Ambient Gases: Stability and Chemical Reactivity. Issue 2 (26th July 2019) - Edla, Raju; Kuo, Chia-Nung; Torelli, Piero; Lue, Chin Shan; Boukhvalov, Danil W.; Politano, Antonio
Abstract : Combining first‐principles calculations with synchrotron‐based X‐ray photoelectron spectroscopy, the surface chemical reactivity of VSe2 single crystals toward oxygen, water, and air is assessed. It is found that the pristine, undefected surface is inert toward oxygen and water adsorption. The presence of Se defects drastically changes the surface reactivity. Specifically, water adsorption at room temperature is dissociative and mainly localized at Se vacancies. In contrast, surface oxidation is achieved only after long‐term air exposure (1 month). These results are crucial to assess the surface stability in ambient environment in the prospect of VSe2 ‐based applications. Abstract : The pristine, undefected surface of bulk VSe2 single crystals is inert toward oxygen and water. The presence of Se vacancies drastically changes surface chemical reactivity. In defective samples, water adsorption at room temperature is dissociative and mainly localized at Se vacancies. Surface oxidation is achieved only after long‐term air exposure (1 month).